Phonological replacement of loan words used in Indonesian - Abdurrahim Abdurrahim; Syahrir Jalil (Politeknik Negeri Bali, 2020)
The aim of the study was to identify the phonological replacement of foreign words (primarily English words) adopted to Indonesian. The method used was descriptive that was to describe how the foreign words change after being adopted into Indonesian and how the phonemes in them change. By adopting a linguistic approach with simple descriptive analysis, the study was successful to analyze many adopted words. The findings of the study indicated that in the process of word adoption some phonemes underwent phonological replacement and some are constant. There are about twenty-six replacements that are successful to reveal, and these replacements are established as formulas (Formulas of phonological replacement).